2020
DOI: 10.1111/ajd.13521
|View full text |Cite
|
Sign up to set email alerts
|

Nail dystrophy as initial presentation of systemic amyloidosis

Abstract: Nail dystrophy as initial presentation of systemic amyloidosisSystemic amyloidosis is a rare group of diseases that result from the extracellular deposition of amyloid protein. In patients with systemic amyloidosis, the most common skin symptoms are petechiae and ecchymoses; nail dystrophy as the initial symptom is rare, with only one previous report.A 50-year-old Chinese man developed bilateral fingernail and toenail lesions without apparent cause, manifested as thickening and destruction of nails followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Amyloidosis is a systemic disease with multiple clinical manifestations because of the deposit of amyloid substance in many tissues and, in rare cases, nail involvement can be the unique cutaneous sign to confirm the disease and avoid overlooked diagnosis. Multiple nail changes were related to amyloidosis, such as longitudinal striations [1-3], onychorrexis [1, 2], splinter hemorrhage [3], pterygium simulating lichen planus [1, 4], pachyonychia [4], and destruction of the nail plate [5]. Our case did not show longitudinal striations as most cases did.…”
Section: Answermentioning
confidence: 74%
See 1 more Smart Citation
“…Amyloidosis is a systemic disease with multiple clinical manifestations because of the deposit of amyloid substance in many tissues and, in rare cases, nail involvement can be the unique cutaneous sign to confirm the disease and avoid overlooked diagnosis. Multiple nail changes were related to amyloidosis, such as longitudinal striations [1-3], onychorrexis [1, 2], splinter hemorrhage [3], pterygium simulating lichen planus [1, 4], pachyonychia [4], and destruction of the nail plate [5]. Our case did not show longitudinal striations as most cases did.…”
Section: Answermentioning
confidence: 74%
“…These 5 cases occurred mainly in male patients (4:1) as the first presentation of systemic amyloidosis (all cases), and it can be related to multiple myeloma (3:2 with no underlying disease). Some studies indicated the improvement of the nail’s lesions as a predictor of treatment response [1, 5].…”
Section: Answermentioning
confidence: 99%
“…Nail involvement is rarely described and can be the unique sign of the disease. 3 It is usually characterized by brittleness, increased fragility, trachyonychia, longitudinal ridging, and subungual splinter hemorrhages. 3,4 Distal onycholysis and anonychia have also been described.…”
Section: Case Historymentioning
confidence: 99%
“…3 It is usually characterized by brittleness, increased fragility, trachyonychia, longitudinal ridging, and subungual splinter hemorrhages. 3,4 Distal onycholysis and anonychia have also been described. The main differential diagnosis is lichen planus.…”
Section: Case Historymentioning
confidence: 99%
See 1 more Smart Citation